Souffleurs de verre, mémoires intimes « au travail » - Marie-Ange Lasmènes (Conserveries Mémorielles)
Glassblowers’ collect of memories realized during an ethnographic investigation shows the interest to observe how a firm holding artistic, social and politic projects can change. After have shown the interest for the ethnologist to study memory in a diachronical way dealing with its temporality, it will be exposed how patrimonialisation of handcrafts offers a new category of heritage localized between national politics and the expansion of a local feeling of identity linked to this corporation expressed by official talks and individual memories. Finally, far from a search of a historical truth of past, some elements of private memories at work, in a glass firm, hidden by the change of an entrepreneurial context and the assimilation of an official memory, will be presented.